2002
DOI: 10.1046/j.1440-1673.2002.01057.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of iatrogenic femoral artery false aneurysms with ultrasound‐guided thrombin injection

Abstract: The aim of this paper is to review our results of treating iatrogenic pseudoaneurysms of the femoral artery with ultrasound-guided thrombin injection. A retrospective review was carried out of all patients referred for this procedure over a 1-year period from December 1999 to December 2000. Forty-five patients were referred and, of these, 44 were eligible for this treatment, with 300-2500 units of thrombin being injected directly into the false aneurysms under ultrasound guidance. The procedure was well tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…This method is now widely used, 1,4,17-33 with a primary success rate ranging from 94% to 100%. 1,4,21,24,27,30,33 In complex cases with multilobated pseudoaneurysms, Ramsay and Marshall 27 observed a lower success rate of 61%. Unresponsiveness to thrombin may be due to vascular injury, so those pseudoaneurysms should probably be repaired surgically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is now widely used, 1,4,17-33 with a primary success rate ranging from 94% to 100%. 1,4,21,24,27,30,33 In complex cases with multilobated pseudoaneurysms, Ramsay and Marshall 27 observed a lower success rate of 61%. Unresponsiveness to thrombin may be due to vascular injury, so those pseudoaneurysms should probably be repaired surgically.…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al 11 modified the technique, which proved successful in 20 of 21 patients in his initial 1998 study. This method is now widely used, 1,4,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] with a primary success rate ranging from 94% to 100%. 1,4,21,24,27,30,33 In complex cases with multilobated pseudoaneurysms, Ramsay and Marshall 27 observed a lower success rate of 61%.…”
Section: Discussionmentioning
confidence: 99%
“…The injection of thrombin is generally well tolerated by patients. Complete obliteration of the pseudoaneurysm is usually achieved within 15-20 seconds [12][13][14][15]. Ramsay et al observed a lower success rate in multilobated FAP [14].…”
Section: Discussionmentioning
confidence: 99%
“…Complete obliteration of the pseudoaneurysm is usually achieved within 15-20 seconds [12][13][14][15]. Ramsay et al observed a lower success rate in multilobated FAP [14]. Sheiman et al proposed surgical repair in patients who did not respond to treatment with thrombin [16].…”
Section: Discussionmentioning
confidence: 99%
“…If unsuccessful, there is a variety of endovascular techniques, safer and simpler than open repair, such as ultrasound‐guided thrombin injection, 2 endovascular coil insertion 3 and/or stent insertions, 4 which might remove the need for majority of open reconstructions.…”
mentioning
confidence: 99%